Swot Analysis In Increasing The Sales Of Wood Products At The Wood Depot Tiga Mandala Putra In Kaur Regency - Setiawan, Riduan; Anggriani, Ida; Febliansa, M Rahman (Universitas Dehasen Bengkulu, 2025)
This study aims to analyze the strengths, weaknesses, opportunities, and threats (SWOT) faced by Depot Kayu Tiga Mandala Putra in Kaur Regency, as well as to formulate appropriate marketing strategies to increase the sales of wood products. The method used is a combination of quantitative and qualitative approaches. Data collection techniques included direct observation, in-depth interviews, questionnaire distribution, and document analysis. Data analysis utilized the IFE (Internal Factor Evaluation) matrix, EFE (External Factor Evaluation) matrix, and SWOT quadrant mapping to determine relevant strategies.The research results indicate that the strategic position of Tiga Mandala Putra Wood Depot is in Quadrant I (aggressive strategy) with an IFE score of 2,39 and an EFE score of 2,22. This indicates that the depot has sufficient internal strengths and significant external opportunities. The recommended strategies include optimizing digital promotions, enhancing service capacity, and developing partnerships with local businesses. The implementation of SWOT-based strategies is expected to significantly increase sales volume and business competitiveness.